03 - EFFECT OF SUPPLEMENTATION WITH FLAXSEED ON LIPID PROFILE AND HEMOGLOBIN LEVELS AND TESTOSTERONE IN ATHLETES AND NONATHLETES (Fiep Bulletin - online, 2011)
Several studies have been conducted with flaxseed (FS) and the realization of much of this is that FS reduces the risk of cardiovascular disease, decreased levels of HDL cholesterol, total cholesterol, among others. The aim of this study was to investigate the effects of supplementation with flax flour on lipid profile (TC, HDL and TRG) and hemoglobin (HMB) and testosterone (T) in nine elite athletes (A), mean age 25.1 and eight non-athletes (NA), with a mean age of 23.5. The participants consumed 30 g / day of LF for 45 days em dinner. Each subject performed a blood sample prior to consumption in 15, 30 and 45 days, without changing the regular diet. The subjects were instructed not to take supplements and medications. The factors analyzed were: HMB, T, HDL and TC. The analysis was performed according to routine procedures of the laboratories. The results: an increase of 15.7% for T in the trained group (P
Keywords: linseed; elite athletes; supplementation